Pope Francis, Islam, and the Ethics of Recognition: Openings and Muslim Responses - Abdessamad Belhaj (Religions)
Through his numerous visits to the Muslim world, and by promoting an ethics of recognition of Islam, Pope Francis built trust and a religious encounter with various Muslim institutions. His dedication to global ethical concerns, such as human brotherhood, the environment, migration, and peace, has made religious leaders throughout the Middle East, particularly in Iraq, Egypt, and the Gulf states, favourable to interfaith co-operation with the Catholic Church for the common good. In particular, Pope Francis has influenced how justice and tolerance are perceived by many in the Muslim world, as evidenced by various Muslim responses to his messages. He was therefore effective in initiating an ethical encounter to overcome injustice and violence, in addition to re-establishing religious diplomacy and communication with Islam.